Predictors of new bone erosion in rheumatoid arthritis patients receiving conventional synthetic disease-modifying antirheumatic drugs: Analysis of data from the DRIVE and DESIRABLE studies. Issue 1 (2nd January 2021) - Takeuchi, Tsutomu; Soen, Satoshi; Ishiguro, Naoki; Yamanaka, Hisashi; Tanaka, Sakae; Kobayashi, Makiko; Okubo, Naoki; Nitta, Takaya; Tanaka, Yoshiya
Abstract: Objective: To investigate new bone erosion and cartilage destruction predictors in rheumatoid arthritis (RA) patients treated with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs). Methods: Placebo-treated patient data from two 12-month, randomized, double-blind, phase 2 (DRIVE) and 3 (DESIRABLE) trials that evaluated denosumab efficacy in csDMARD-treated RA patients were used. Change from baseline in erosion score (ES) of ≥1.0 at 12 months was considered new bone erosion; predictors were identified using a multivariate model. Results: Among 306 patients, mean ± standard deviation disease activity score 28–C-reactive protein (CRP) at baseline was 3.58 ± 1.03. New bone erosion was observed in 90 patients (29.4%). Univariate analysis identified female sex, anti-cyclic citrullinated peptide (CCP) antibody positivity, rheumatoid factor (RF) positivity, tender joint count ≥6, CRP ≥0.3 mg/dL, erythrocyte sedimentation rate (ESR) ≥28 mm/h, and baseline ES ≥3 as significant predictors for new bone erosion. In multivariate analysis, predictors were anti-CCP antibody positivity, CRP ≥0.3 mg/dL, and baseline ES ≥3; RF and ESR were excluded as they strongly correlated with anti-CCP antibody and CRP, respectively. Conclusion: In RA patients treated with csDMARDs, new bone erosion predictors were seropositivity, elevated inflammatory markers, and baseline ES ≥3. Trial registration number: DRIVE, JapicCTI-101263; DESIRABLE, NCT01973569